2001
DOI: 10.1093/toxsci/61.1.92
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Induced by Red Food Dyes Orally Administered to Pregnant and Male Mice

Abstract: We determined the genotoxicity of synthetic red tar dyes currently used as food color additives in many countries, including JAPAN: For the preliminary assessment, we treated groups of 4 pregnant mice (gestational day 11) once orally at the limit dose (2000 mg/kg) of amaranth (food red No. 2), allura red (food red No. 40), or acid red (food red No. 106), and we sampled brain, lung, liver, kidney, glandular stomach, colon, urinary bladder, and embryo 3, 6, and 24 h after treatment. We used the comet (alkaline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(138 citation statements)
references
References 38 publications
4
127
0
2
Order By: Relevance
“…Hence they have been reported as renowned mutagenic and clastogenic agents. Previous studies suggested food color as one of the best known chemical mutagens as it reacts with biomolecules including DNA and damages their structure and biological activity (Tsuda et al, 2001;Das and Mukherjee, 2004), leading to genetic alterations in DNA molecules. According to Rus et al (2010), tartrazine and carmoisine were found to have hepatotoxic and nephrotoxic action, causing congestion, stasis, and edema in the liver and kidney, hepatocyte and kidney apoptosis, and atrophy of some renal corpuscles.…”
Section: Discussionmentioning
confidence: 99%
“…Hence they have been reported as renowned mutagenic and clastogenic agents. Previous studies suggested food color as one of the best known chemical mutagens as it reacts with biomolecules including DNA and damages their structure and biological activity (Tsuda et al, 2001;Das and Mukherjee, 2004), leading to genetic alterations in DNA molecules. According to Rus et al (2010), tartrazine and carmoisine were found to have hepatotoxic and nephrotoxic action, causing congestion, stasis, and edema in the liver and kidney, hepatocyte and kidney apoptosis, and atrophy of some renal corpuscles.…”
Section: Discussionmentioning
confidence: 99%
“…of single oral doses of allura red (Tsuda et al, 2001). Comet assay was used to assess DNA damage in the embryo at 3, 6 and 24 h sampling times.…”
Section: In Vivo Assaysmentioning
confidence: 99%
“…urticaria, asthma), especially when administered in mixes with other synthetic colour additives [67].…”
Section: In Pharmaceutical Industrymentioning
confidence: 99%